Representatividade no Tribunal do Júri brasileiro : críticas à seleção dos jurados e propostas à luz do modelo americano - Brochado Neto, Djalma Alvarez (2016)
Popular participation is the main characteristic of the jury. In this vein, the study of the composition of the Brazilian jury is of utmost importance for the evolution of this institute. Thus, the homogeneity identified between some aspects of the jurors, especially in Fortaleza, compromises its democratic character. In the United States - "Land of the Jury" - the search for a representative and impartial venire occurs for centuries in the higher courts, seeking to minimize the discrimination of gender and race, for example, providing inspiration to changes in forensic practice and legislation in the Brazilian model. This study is focused on surveys among jurors in Brazil, including the one held in the five (5) courts of Fortaleza in 2016, in an attempt to reveal the profile of the jurors, identifying procedures that prevent better representation of the main social groups in the jury. Then, it made a study of the American jury pool, describing, through Supreme Court decisions, the evolution of the jurors selection process. It suggests practical and legal changes to the Brazilian system, as an opportunity to argue to the jury (called in the United States as voir dire) for example, aiming to increase popular participation and reduce partiality in jury trials. It is concluded, after studying some bills pending in federal legislative houses (including the new Criminal Procedure Code), despite the legislator's effort, the jury in Brazil, especially in big cities, is in fact constituted by a defined juror profile: public servant, graduate or specialization, married, over the age of forty (40) years, with income between four (4) and 10 (ten) minimum wages, and the bills do not provide change this outlook. The ongoing discussions about the new Criminal Procedure Code elevates the relevance of this study in an attempt to strengthen this trial model, fundamental right in Brazil, therefore, entrenchment clause in the Federal Constitution.